Effect Soak Feet With Warm Water To Level Of Anxiety In Pregnant Women Trimester III Pegandon Kendal Public Health Center - Putri Damarsanti; Rina Anggraini; Setianingsih Setianingsih (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction:Anxiety during pregnancy in the first, second and third trimester is very likely to occur, especially on the third trimester of pregnancy approaching labor time. Anxiety can be reduced in various ways,for instanceby having positive thinking, praying, story sharing with others, meditation, and hydrotherapy. One form of hydrotherapy issoaking feet in warm water. This research aims to find out the effect of soaking feet in warm water towards the anxiety levelsof the third trimester pregnant women at Pegandon Community Health Centre in Kendal. This research used quasi experimental time series design without comparison group. The samples are 36 respondents were taken by purposive sampling. The instrument used is Hamilton anxiety level questionnaire sheet and observation sheet. The data is analyzed by Wilcoxon test. The result shows there are effects of soaking feet in warm water towards the the third trimester pregnant women’s anxiety levels at Pegandon Community Health Centre in Kendal with 0,000 < 0,05 p-value. The writer hopes third trimester pregnant women who experience anxiety can soaking feet in warm water as an alternative therapy for anxiety.